The appropriate use of risk scores in the prediction of atrial fibrillation - O’Neal, Wesley T.; Alonso, Alvaro (Journal of Thoracic Disease, 2016)
Atrial fibrillation (AF) is the most common arrhythmia encountered in clinical practice (1).